Comparative Study of Islamic Family Law in Indonesia and Saudi Arabia: Maqāṣid Al-Sharī'ah Perspective - Fatahillah, Wilnan; Luhuringbudi, Teguh (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This study explores the comparative implementation (substance, form, and interpretation) of Islamic family regulation in Indonesia and Saudi Arabia through the lens of Maqāṣid al-Sharī’ah. This research paper aims to reveal how the two countries differ in presenting the normativity (in terms of substance, form, and interpretation) of the regulation. This study uses primary sources from legal documents and academic literature, as well as qualitative data. In-depth analysis shows that the flexibility and rigidity of regulation in both countries are based on the principles of justice and social protection, although the methods of manifestation are different. The main findings indicate that although Saudi Arabia is known for its strict regulation, there is a courtroom that considers individual conditions, while Indonesia shows legal initiatives to address social challenges. The novelty of this study lies in the emphasis that Islamic regulation can adapt to contemporary contexts without losing the essence of Sharī’ah despite geographical differences. Limitations of the study include the lack of detailed field case studies, prompting further research directions to link law to social manifestations directly. Suggestions for further research include deeper qualitative analysis of the application of law in more diverse social contexts. This research adds a new dimension to the study of Islamic law as a dynamic and responsive, yet responsible, instrument.